The Impact of Boarding House Development on Community Economic Activities in Jempong Baru Village, Sekarbela District, Mataram City - Vera Supriastuti; Muaidy Yasin; Iwan Harsono (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
This study aims to determine the impact of boarding house development on the economic activities of the community in Jempong Baru Village, Sekarbela District, Mataram City. This study is a descriptive qualitative study. The determination of the sample in this study used a purposive sampling technique. The location of this study is in Jempong Baru Village, Sekarbela District, Mataram City. The data collection procedure used observation, interviews, and documentation. The validity of the data in this study used triangulation of sources, techniques, and time. Data analysis used the Miles and Huberman interactive data analysis model which is divided into data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are 3 impacts of boarding house development, namely: 1) Boarding house development can open up many new job opportunities for the surrounding community, when boarding houses start operating, indirectly there will be more students living in the area. This will encourage the emergence of new businesses or expand existing businesses, with the increase in these businesses the surrounding community can get jobs as employees or open their own businesses. So, directly or indirectly, the construction of boarding houses helps reduce the number of unemployed in the area. 2) The construction of boarding houses has a very good impact on community income. The impact of economic activities carried out by the community will support increasing community income. The construction of boarding houses also creates a shift in economic activities carried out by the community.